Гидродинамика закрученного потока в канале циклонного охлаждения лопатки ГТД - Халатов, А. А.; Борисов, И. И.; Дашевский, Ю. Я.; Северин, С. Д. (Eastern-European Journal of Enterprise Technologies, 2009)
The results of experimental study of swirling flow hydrodynamics in an open cylindrical channel are considered. The channel diameter is 20 mm, the length is 280 mm; it was supplied with tangential swirl generator at the inlet. The static and total pressure fields, surface swirl flow angle, hydraulic losses in the channel and tangential swirl generator are given